Performance assessment of a thermoelectric module by using rotating circular cylinders and nanofluids in the channel flow for renewable energy applications - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Sci Ltd, 2021)
In the present study, a novel thermal flow system configuration is offered with rotating cylinders and nanofluids in channel to increase the powers generated in the TEG module mounted between the channels. The 3D coupled heat transfer, fluid flow and electric field equations are solved with finite element method. The numerical study is performed for different Reynolds number (between 350 and 1000), rotational Reynolds number (between -4000 and 4000), number (between 1 and 5), size (between 0 and 0.2H), location of the circular cylinders and solid CNT nanoparticle volume fraction (between 0 and 0.02). It is observed that as the cylinders are used in the channel with rotation, power enhancements of TEG module are achieved. When reference case of no-cylinder is compared, power increments of 56.5% and 27.5% are achieved for rotational Reynolds number of -3000 at Reynolds number of 350 and 1000. Higher number of cylinders provide higher power enhancements in the module and with five cylinders rotating at the highest speed, increments up to 47% are obtained at Reynolds number of 1000. Size and location of the cylinders are also found o be effective in altering the power features of the TEG module. Inclusion of nanoparticle is found to be efficient in the TEG power enhancement when performance of the system is low. Thus, slight improvement is achieved with nanoparticles when system with five cylinder at the highest speed and highest Reynolds number is considered. A reduced order model which is based on proper orthogonal decomposition methods is used to predict the temperature variations in the coupled domains and to effectively calculate the power generated in the TEG module. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: TEG; Rotating cylinders; Numerical simulation; Thermoelectric energy; Finite element method; CNT-Nanofluid